Partial discharge observation of a complex insulation structure model and residual space charge characteristics investigation under repeated lightning impulses. Issue 6 (22nd March 2021) - Lu, Li; Ichimura, Satoshi; Rokunohe, Toshiaki
Abstract: In this research, the authors concentrated on a rarely studied part in the power transformer's insulation structure: the connection part of radial and axial spacers. An experimental model was constructed to simulate this part. It was experimentally observed that the partial discharge starting in the oil gap created by the axial and radial spacers. Characteristics of the abovementioned partial discharge under repeated lightning impulses were also investigated. A longer interval time seemed to accelerate the insulation property deterioration of the constructed model, which is contrary to those reported in other studies. It was because that the partial discharge occurrence was prevented by the residual space charge at the surface of oil/insulation if the time interval of the repeated impulses was not long enough. Therefore, it is proposed that a long enough interval time or a polarity test is expected in the factory test to exclude the influence of the residual space charge and understand the real insulation property of power transformers.